Stratigraphic and Structural Framework of Upper Middle Ordovician Rocks in the Head Lake-Burleigh Falls Area of South-Central Ontario - Sanford, Bruce (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1993)
ABSTRACTField investigations in the Head Lake-Burleigh Falls area of south-central Ontario, that focused mainly on the Covey Hill(?), Shadow Lake, Gull River and Coboconk formations along the Paleozoic escarpment, provided clear evidence of faulting. Observed and inferred structural deformation, coupled with faciès changes within the Shadow Lake and lower Gull River, point to a succession of basement movements during the Phanerozoic. These range from Hadrynian-Early Cambrian, through Middle Ordovician to post-late Middle Ordovician times. Some of the earlier movements (Hadrynian-Early Cambrian to late Middle Ordovician) appear to be coincident with, and probably related to, plate tectonic events and the associated Taconian orogeny that were in progress along the southeastern margins of the North American continent. Post-Middle Ordovician block faulting, on the other hand, may have been triggered by any number of epeirogenic events related to late stage Taconian, Acadian or Alleghanian orogenies in Late Ordovician to Carboniferous times, or possibly to rifting associated with continental break-up and initiation of seafloor spreading processes in the early Mesozoic. Manuscrit révisé accepté le 5 août 1993